Describing art - an interdisciplinary approach to the effects of speaking on gaze movements during the beholding of paintings - Klein, Christoph; Engelbrecht, Martina (PLOS ONE, 2014)
Ever since the Renaissance speaking about paintings has been a fundamental approach for beholders, especially experts. However, it is unclear whether and how speaking about art modifies the way we look at it and this was not yet empirically tested. The present study investigated to the best of our knowledge for the first time in what way speaking modifies the patterns of fixations and gaze movements while looking at paintings. Ninety nine university students looked at four paintings selected to cover different art historical typologies for periods of 15 minutes each while gaze movement data were recorded. After 10 minutes, the participants of the experimental group were asked open questions about the painting. Speaking dramatically reduced the duration of fixations and painting area covered by fixations while at the same time increasing the frequencies of fixations, gaze length and the amount of repeated transitions between fixation clusters. These results suggest that the production of texts as well-organised sequences of information, structures the gazes of art beholders by making them quicker, more focused and better connected.
Gesehen am 23.10.2020